The matter of "unbalance" in right dominant atrioventricular septal defect - Ignacio Lugones; María Fernanda Biancolini; Germán Lugones; Julio César Biancolini; Ana M S de Dios (Wolters Kluwer Medknow Publications, 2019)
Unbalance in atrioventricular septal defect can be found in more than one anatomic level and in different degrees at each level. The definition of "unbalance" has historically been focused in comparing the dimensions of main cardiac structures, such as the atrioventricular valve and the ventricles. However, the hemodynamic aspects of unbalance need to be considered as having, at least, similar relevance. New concepts and already described parameters must be combined and understood as a whole to help the surgical decision-making process.